Appropriate writing assessment, how do we do it properly? - Putra, Martin Surya (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2011)
This paper describes the assessment upon the 3rd semester Business Administration studentsâ writing work of State Polytechnics Samarinda. Results show that there are weaknesses done by the English lecturer of this Polytechnics in evaluating his studentsâ work: 1) Instructions given to his students were not clear for examples: how many pages or how many words they had to write, resulting in a very short paragraphs, a very long paragraph written by students, 2) criteria of assessment were not clear, reflected by his own judgment and interpretation in form of words like: good, fair, excellent; 3) Students were not given a feedback on what they had written in form of the first draft and neither were they told to rewrite the first draft for final product.Â